Current alcohol, tobacco, and khat use and associated factors among adults living in Harari regional state, eastern Ethiopia: A community-based cross-sectional study - Bete, Tilahun; Lami, Magarsa; Negash, Abraham; Eyeberu, Addis; Birhanu, Abdi; Berhanu, Bekelu; Abdeta, Tilahun; Nigussie, Shambel; Dechasa, Deribe Bekele; Gemechu, Kabtamu; Wedaje, Dawud; Alemu, Ayichew; et al. (Frontiers in Psychiatry, 2022)
Background: Psychoactive substance use become a major public health and socioeconomic problem worldwide. Despite its burden and consequences, there is no community-based study conducted on psychoactive substance use and associated factors in eastern Ethiopia. Therefore, this study aimed to assess the magnitude and determinants of current alcohol, tobacco, and khat among adults living in the Harari regional state, Eastern Ethiopia. Methods: A community-based cross-sectional study was done on 955 adults living in Harari regional state. Participants were randomly recruited using a simple random sampling technique. Data was collected by interviewer-administered structured and semi-structured questionnaires. Data were entered into Epi Data version 3.1 and exported to Stata Version 14.0 for analysis. Logistic regression analysis was done to determine the association between the outcome and independent variables and the statistical significance was declared at a p-value of <0.5. Result: Of 955 eligible participants, 95.29% participated in the study. The overall prevalence of current alcohol use, Tobacco use, and Khat use in this study was 8.24%, 14.5%, and 63.30% respectively. The availability of alcohol, being unemployed, and being a current khat user were significantly associated with current alcohol use. Being male, having a low level of education, having peer pressure, having a common mental disorder, being a current alcohol user, and being khat user were identified as significant predictors for current tobacco use. The age between 31- 40, being a Muslim religion follower, being a farmer, being a current tobacco user, and availability of khat were significantly associated with current khat use. Conclusion and Recommendations: The prevalence of psychoactive substance use in the study area was relatively high compared to previous studies. By considering these determinants, screening, early identification, and developing appropriate intervention strategies to prevent and tackle current alcohol, tobacco, and Khat use in the community should be of great concern.